Efficient Implementations of Gauss-Based Sieving Algorithms - Satilmis, Hami; Akleylek, Sedat (IEEE, 2020)
The security of lattice-based cryptosystems in post-quantum cryptography is mainly based on the difficulty of solving the shortest vector problem (SVP) or the closest vector problem (CVP). In this paper, efficient implementations of GaussSieve and ProGaussSieve algorithms alternatives to solve the shortest vector problem are studied. A cryptographic software library is developed which is an infrastructure for the implementation of sieving algorithms in order to have faster running times than the ones in the literature. In addition, a comparison table including the running times of the implementations of GaussSieve and ProGaussSieve algorithms is presented. According to the experimental results, the proposed GaussSieve and ProGaussSieve implementations are much more faster and efficient than the others.
Keywords: Lattice-Based Cryptography; Sieving Algorithms; Gausssieve; Progausssieve; Svp